Fine-structure high-stability fused-cast corundum refractory and preparation method thereof
Patent Information
- Application Number
- CN202611100254.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-20
AI Technical Summary
[0006]为了克服现有技术中耐火材料存在的晶界结合强度不足、组织结构不够致密、热震稳定性较差以及长期高温服役过程中易产生微裂纹和结构失稳问题,本发明的目的在于提供一种细密结构高稳定性耐火材料及其制备方法
本发明通过磷酸二氢铝与氧氯化锆对氧化铝骨料进行协同改性,在骨料表面形成稳定的协同界面结构,提高了骨料与熔体之间的润湿结合能力,并促进熔体均匀分散及凝固过程中晶体稳定生长,从而有效降低材料内部缺陷和弱界面区域。与此同时,磷酸钙能够调控熔体凝固过程中的晶界发育,提高凝固组织均匀性,减少缩孔及偏析缺陷;氧化钛能够抑制晶粒异常长大并增强晶界稳定性;稳定化氧化锆、氧化镁及氧化钇之间形成协同增韧和稳定化作用,有效缓解高温环境下的热应力集中现象。通过上述组分的协同作用,使所得耐火材料形成更加细密均匀的微观结构,显著提高材料的耐压强度、热震稳定性及高温抗侵蚀性能,同时降低显气孔率,提高长期高温服役条件下的结构稳定性和使用寿命。
Smart Images

Figure FT_1 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of refractory materials and high-temperature inorganic non-metallic materials, specifically relating to a fine-structure, highly stable fused cast corundum refractory material and its preparation method. Background Technology
[0002] Refractory materials are a class of functional materials that combine high-temperature resistance, wear resistance, corrosion resistance, and high mechanical strength. They are widely used in metallurgy, power, building materials, chemical industry, mining, and solid waste treatment, and are particularly suitable for conveying high-temperature particulate matter, high-temperature flue gas, molten slag, and corrosive media. With the development of modern industrial equipment towards larger scale, higher temperatures, and long-term continuous operation, higher requirements are placed on the structural stability, thermal shock resistance, and high-temperature service life of refractory materials.
[0003] Currently, cast corundum refractories are mainly composed of refractory raw materials such as alumina, tabular corundum, and zirconium oxide. These are melted at high temperatures in an electric arc furnace, cast into shape, and then annealed to form a stable and dense cast structure. Although existing materials possess high refractoriness and wear resistance, they are still prone to problems such as insufficient grain boundary bonding strength, high porosity, and poor microstructure uniformity during long-term high-temperature service. Especially under conditions of high-temperature erosion and frequent thermal cycling, microcracks easily form within the material and gradually propagate, leading to a decrease in thermal shock resistance. In severe cases, localized spalling and failure may occur, thus affecting the service life of the refractory material.
[0004] To improve the overall performance of cast corundum refractories, existing technologies typically employ the addition of stabilizing components such as zirconium oxide, magnesium oxide, and yttrium oxide, along with optimization of the melting process and solidification microstructure, to enhance material uniformity and structural stability. However, most solutions rely primarily on component stacking or a single reinforcement mechanism, lacking sufficient synergistic control over the surface interface structure and grain boundary regions of the refractory aggregate. This makes it difficult to simultaneously achieve microstructure refinement, high-temperature structural stability, and thermal shock resistance. Furthermore, during the melting and solidification process, insufficient melt uniformity, inadequate solidification rate control, and insufficient thermal stress release can easily lead to the formation of localized pores, weak interfaces, and stress concentration areas, thus limiting further improvements in the material's overall performance.
[0005] Therefore, developing a fine-structured, highly stable refractory material and its preparation method that can synergistically regulate the interface structure of alumina aggregate and promote grain boundary densification and microstructure homogenization is of great significance for improving the high-temperature mechanical properties, thermal shock resistance, and long-term service stability of refractory materials. Summary of the Invention
[0006] To overcome the problems of insufficient grain boundary bonding strength, insufficiently dense microstructure, poor thermal shock stability, and susceptibility to microcracks and structural instability during long-term high-temperature service in existing refractory materials, this invention aims to provide a fine-structured, highly stable refractory material and its preparation method. This invention uses aluminum dihydrogen phosphate-zirconia oxychloride synergistically modified alumina aggregate as the main refractory aggregate. Aluminum dihydrogen phosphate and zirconium oxychloride construct a synergistically modified interface layer on the surface of the alumina aggregate, improving the interfacial bonding ability between the aggregate and the matrix. Simultaneously, a multiphase synergistic reinforcement system is constructed by combining tabular corundum, stabilized zirconium oxide, magnesium oxide, yttrium oxide, silica powder, calcium phosphate, and titanium oxide. Calcium phosphate is used to regulate grain boundary development during melt solidification, improve microstructure uniformity, and reduce shrinkage cavities and segregation defects. Zirconia, magnesium oxide, and yttrium oxide are used to improve the structural stability and thermal shock resistance of the material, while titanium oxide is used to improve the grain boundary structure and inhibit abnormal grain growth. By mixing, aging, pressing, melting and casting, pouring and annealing, a refractory material with uniform structure, fine texture, and excellent high-temperature stability is obtained. The fine-structured, high-stability refractory material prepared by this invention has the characteristics of low apparent porosity, uniform structure, strong interfacial bonding, excellent thermal shock resistance, strong high-temperature erosion resistance, and good long-term service stability.
[0007] The objective of this invention can be achieved through the following technical solutions: A fine-structured, highly stable refractory material comprises the following raw materials in parts by weight: 80-140 parts of aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina aggregate; 20-80 parts of tabular corundum; 3-20 parts of stabilized zirconium oxide; 1-10 parts of magnesium oxide; 0.5-8 parts of yttrium oxide; 2-15 parts of silica powder; 3-15 parts of calcium phosphate; and 0.5-5 parts of titanium oxide. The aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina aggregate is prepared by synergistic modification of alumina aggregate with aluminum dihydrogen phosphate and zirconium oxychloride.
[0008] Optionally, the aluminum dihydrogen phosphate-zirconia oxychloride co-modified alumina aggregate comprises the following raw materials in parts by weight: 80-150 parts alumina aggregate; 3-20 parts aluminum dihydrogen phosphate; 2-15 parts zirconia oxychloride; 30-120 parts ethanol; and 40-150 parts deionized water.
[0009] Optionally, the preparation method of aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina aggregate includes the following steps: (1) Add aluminum dihydrogen phosphate to a mixed solvent of ethanol and deionized water and stir to dissolve. Then add zirconium oxychloride and continue stirring to obtain aluminum dihydrogen phosphate-zirconium oxychloride precursor solution. (2) Add aluminum oxide aggregate to the aluminum dihydrogen phosphate-zirconia oxychloride precursor solution for dispersion treatment, so that aluminum dihydrogen phosphate and zirconium oxychloride are uniformly loaded on the surface of aluminum oxide aggregate; (3) The obtained material is aged, filtered, washed and dried to obtain aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina aggregate.
[0010] Optionally, the reaction conditions in step (1) are to stir at 400-800 rpm for 0.5-3 h at 50-70 °C, followed by the addition of zirconium oxychloride and continued reaction for 1-4 h.
[0011] Optionally, the reaction conditions in step (2) are to disperse the mixture at 500-1000 rpm for 1-5 hours at 60-90°C.
[0012] Optionally, the aging conditions in step (3) are aging at 40-80℃ for 6-24 hours; the drying conditions in step (3) are drying at 100-150℃ for 6-24 hours.
[0013] Optionally, the stabilized zirconium oxide is yttrium stabilized zirconium oxide; the particle size of the magnesium oxide is 1-10 μm; the SiO2 content of the silicon micropowder is 92%-98%; and the particle size of the titanium oxide is 0.1-5 μm.
[0014] Optionally, a method for preparing a fine-structured, highly stable refractory material includes the following steps: S1, Weigh and mix aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina aggregate, tabular corundum, stabilized zirconium oxide, magnesium oxide, yttrium oxide, silica powder, calcium phosphate and titanium oxide to obtain basic mixture; S2, the basic mixture is directly added to the electric arc furnace for melting; S3 involves melting the basic mixture in an electric arc furnace for 2 hours and then directly casting it to obtain a fine-structured, highly stable fused cast corundum refractory material.
[0015] Optionally, the reaction conditions for step S1 are to mix and stir at 500-1000 rpm for 1-4 hours at 25-50°C to obtain the basic mixture.
[0016] Optionally, the reaction conditions for step S2 are as follows: the basic mixture is directly added to the electric arc furnace and melted at 1850–2050°C for 2 hours; after melting, casting is carried out immediately.
[0017] The beneficial effects of this invention are: This invention synergistically modifies alumina aggregate with aluminum dihydrogen phosphate and zirconium oxychloride, forming a stable synergistic interface structure on the aggregate surface. This improves the wetting and bonding ability between the aggregate and the melt, promotes uniform melt dispersion and stable crystal growth during solidification, thereby effectively reducing internal defects and weak interface regions in the material. Simultaneously, calcium phosphate regulates grain boundary development during melt solidification, improving the uniformity of the solidified structure and reducing shrinkage cavities and segregation defects; titanium oxide inhibits abnormal grain growth and enhances grain boundary stability; and the synergistic toughening and stabilizing effects of stabilized zirconium oxide, magnesium oxide, and yttrium oxide effectively alleviate thermal stress concentration under high-temperature conditions. Through the synergistic effect of these components, the resulting refractory material forms a finer and more uniform microstructure, significantly improving its compressive strength, thermal shock stability, and high-temperature erosion resistance, while reducing apparent porosity and improving structural stability and service life under long-term high-temperature service conditions. Attached Figure Description
[0018] The invention will now be further described with reference to the accompanying drawings.
[0019] Figure 1 A comparison chart showing the thermal shock stability test results of samples with different ratios. Detailed Implementation
[0020] The present invention will be further described below with reference to specific embodiments. However, the present invention is not limited to the following embodiments. Equivalent adjustments made without departing from the spirit and essence of the present invention should also be considered to fall within the protection scope of the present invention.
[0021] Example 1: The purpose of this example is to verify the feasibility of preparing a fine-structured, highly stable refractory material using the lower limit ratio of each component and under relatively low reaction conditions.
[0022] S1. Add 3 parts of aluminum dihydrogen phosphate to a mixed solvent consisting of 30 parts of ethanol and 40 parts of deionized water, and stir at 400 rpm for 0.5 h at 50 °C to ensure complete dissolution. Then add 2 parts of zirconium oxychloride and continue stirring for 1 h to obtain an aluminum dihydrogen phosphate-zirconium oxychloride precursor solution. Then add 80 parts of alumina aggregate and stir at 500 rpm for 1 h at 60 °C. Aged the obtained material at 40 °C for 6 h, filtered, washed, and dried at 100 °C for 6 h to obtain aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina aggregate. S2. Add 90 parts of aluminum dihydrogen phosphate-zirconium oxychloride co-modified alumina aggregate, 25 parts of tabular corundum, 5 parts of stabilized zirconia, 2 parts of magnesium oxide, 1 part of yttrium oxide, 3 parts of silica powder, 4 parts of calcium phosphate and 1 part of titanium oxide into a mixer and mix at 500 rpm for 1 hour at 25°C to obtain the basic mixture. S3. The basic mixture is directly added to the electric arc furnace and melted at 1900℃ for 2 hours. It is then immediately cast into a fine-structured, highly stable refractory material. The material is then pressed and molded. The pressed blank is placed in the electric arc furnace and melted at 1900℃ for 1 hour. It is then poured into a preheated mold and homogenized at 1450℃ for 1 hour. After that, it is annealed at 850℃ for 6 hours and finally cooled to room temperature with the furnace to obtain a fine-structured, highly stable refractory material.
[0023] Example 2: The purpose of this example is to verify the effect of aluminum dihydrogen phosphate-zirconium oxychloride synergistic modification of the interface structure on the formation of fine structure and high-temperature stability of refractory materials when the components are in the median ratio and under moderate reaction conditions.
[0024] S1. 11.5 parts of aluminum dihydrogen phosphate were added to a mixed solvent consisting of 75 parts of ethanol and 95 parts of deionized water. The mixture was stirred at 600 rpm for 1.5 h at 60 °C to ensure complete dissolution. Then, 8.5 parts of zirconium oxychloride were added and the reaction was continued for 2.5 h to obtain an aluminum dihydrogen phosphate-zirconium oxychloride precursor solution. Then, 115 parts of alumina aggregate were added and dispersed at 750 rpm for 3 h at 75 °C. The resulting material was aged at 60 °C for 12 h, filtered, washed, and dried at 120 °C for 12 h to obtain aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina aggregate. S2. Add 110 parts of aluminum dihydrogen phosphate-zirconium oxychloride co-modified alumina aggregate, 50 parts of tabular corundum, 12 parts of stabilized zirconia, 5 parts of magnesium oxide, 4 parts of yttrium oxide, 8 parts of silica powder, 8 parts of calcium phosphate and 2 parts of titanium oxide into a mixer and mix at 750 rpm for 2 hours at 35°C to obtain the basic mixture. S3. The basic mixture is directly added to the electric arc furnace and melted at 1960℃ for 2 hours. After melting, it is immediately cast into a fine-structured, highly stable refractory material. Then, it is pressed into shape. The pressed blank is placed in the electric arc furnace and melted at 1960℃ for 1.5 hours. Then it is poured into a preheated mold and homogenized at 1500℃ for 2 hours. After that, it is annealed at 900℃ for 12 hours. Finally, it is cooled to room temperature with the furnace to obtain a fine-structured, highly stable refractory material.
[0025] Example 3: The purpose of this example is to verify the performance of a fine-structured, highly stable refractory material prepared under the upper limit ratio of each component and under high reaction conditions.
[0026] S1. Add 20 parts of aluminum dihydrogen phosphate to a mixed solvent consisting of 120 parts of ethanol and 150 parts of deionized water, and stir at 800 rpm for 3 hours at 70°C to ensure complete dissolution. Then add 15 parts of zirconium oxychloride and continue stirring for 4 hours to obtain an aluminum dihydrogen phosphate-zirconium oxychloride precursor solution. Then add 150 parts of alumina aggregate and stir at 1000 rpm for 5 hours at 90°C. Aged the obtained material at 80°C for 24 hours, filtered, washed, and dried at 150°C for 24 hours to obtain aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina aggregate. S2. Add 135 parts of aluminum dihydrogen phosphate-zirconium oxychloride co-modified alumina aggregate, 75 parts of tabular corundum, 18 parts of stabilized zirconia, 8 parts of magnesium oxide, 5 parts of yttrium oxide, 13 parts of silica powder, 13 parts of calcium phosphate and 4 parts of titanium oxide into a mixer and mix at 1000 rpm for 4 hours at 50°C to obtain the basic mixture. S3. The basic mixture is directly added to the electric arc furnace and melted at 2020℃ for 2 hours. After melting, it is immediately cast into a fine-structured, highly stable refractory material. Then, it is pressed into a blank and placed in the electric arc furnace to melt at 2020℃ for 2.5 hours. Then, it is poured into a preheated mold and homogenized at 1550℃ for 3 hours. After that, it is annealed at 1000℃ for 20 hours and finally cooled to room temperature with the furnace to obtain a fine-structured, highly stable refractory material.
[0027] Comparative Example 1: The purpose of this comparative example is to verify the effect of aluminum dihydrogen phosphate as a single modified alumina aggregate on the performance of refractory materials.
[0028] S1. Add 11.5 parts of aluminum dihydrogen phosphate to a mixed solvent consisting of 75 parts of ethanol and 95 parts of deionized water, and stir at 600 rpm for 1.5 h at 60°C to ensure complete dissolution; then add 115 parts of alumina aggregate, and stir at 750 rpm for 3 h at 75°C; age the resulting material at 60°C for 12 h, filter, wash, and dry at 120°C for 12 h to obtain aluminum dihydrogen phosphate modified alumina aggregate; Steps S2 and S3, as well as the amounts of each component, are exactly the same as in Example 2.
[0029] Comparative Example 2: The purpose of this comparative example is to verify the effect of zirconium oxychloride-modified alumina aggregate on the performance of refractory materials.
[0030] S1. Add 8.5 parts of zirconium oxychloride to a mixed solvent consisting of 75 parts of ethanol and 95 parts of deionized water, and stir at 600 rpm for 2.5 h at 60 °C; then add 115 parts of alumina aggregate, and stir and disperse at 750 rpm for 3 h at 75 °C; age the resulting material at 60 °C for 12 h, filter, wash, and dry at 120 °C for 12 h to obtain zirconium oxychloride modified alumina aggregate; Steps S2 and S3, as well as the amounts of each component, are exactly the same as in Example 2.
[0031] Comparative Example 3: The purpose of this comparative example is to verify the effect of calcium phosphate on the formation of fine structure and high-temperature stability of refractory materials.
[0032] S1. Prepare aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina aggregate according to the method of Example 2; S2. Add 110 parts of aluminum dihydrogen phosphate-zirconium oxychloride co-modified alumina aggregate, 50 parts of tabular corundum, 12 parts of stabilized zirconia, 5 parts of magnesium oxide, 4 parts of yttrium oxide, 8 parts of silica powder and 2 parts of titanium oxide into a mixer and mix at 750 rpm for 2 hours at 35°C to obtain the basic mixture. S3. The basic mixture is directly added to the electric arc furnace and melted at 1960℃ for 2 hours. After melting, it is immediately cast into a refractory material. Then, it is pressed into a blank and placed in the electric arc furnace to melt at 1960℃ for 1.5 hours. Then, it is poured into a preheated mold and homogenized at 1500℃ for 2 hours. After that, it is annealed at 900℃ for 12 hours and finally cooled to room temperature with the furnace to obtain the refractory material.
[0033] Performance testing: 1. Thermal shock stability test method The fused cast corundum refractory materials prepared in the examples and comparative examples were processed into standard samples with dimensions of 230mm×114mm×65mm and dried at 110℃ for 24h. Then, the samples were placed in a high-temperature furnace at 1100℃ and kept at that temperature for 30min to ensure uniform heating. They were then quickly removed and cooled in flowing cold water at 20℃ for 10min, followed by natural drying for 5min. The above high-temperature heating-water cooling cycle was repeated until through cracks, obvious spalling, or mass loss exceeding 20% of the original mass of the sample appeared on the sample surface. The number of thermal shock cycles that the sample could withstand was recorded to evaluate the thermal shock stability of the material.
[0034] 2. Method for testing compressive strength at room temperature The fused cast corundum refractory materials prepared in the examples and comparative examples were processed into 50mm×50mm×50mm cubic specimens and dried at 110℃ for 24h to constant weight. Subsequently, the specimens were subjected to compression tests using an electronic universal testing machine. The specimens were placed in the center of the compression fixture and continuously pressurized at a loading rate of 5mm / min until the specimens were completely destroyed. The maximum load value at the time of specimen destruction was recorded, and the room temperature compressive strength was calculated according to the pressure area of the specimens. Each group of specimens was tested in parallel 3 times, and the average value was taken as the final test result to evaluate the overall structural stability of the material.
[0035] 3. Apparent porosity test method The fused cast corundum refractory materials prepared in the examples and comparative examples were processed into regular block samples and dried at 110°C to constant weight. The dried mass of the samples was recorded. Then, the samples were completely immersed in boiling water for 2 hours to remove the air inside the samples. They were then soaked at room temperature for another 24 hours to allow the pores inside the samples to fully absorb water. After that, the dry weight, suspended weight and saturated weight of the samples were measured respectively, and the apparent porosity of the material was calculated based on the mass change. Each group of samples was tested in parallel 3 times, and the average value was taken as the final result to evaluate the density of the internal structure of the material.
[0036] 4. High-Temperature Erosion Resistance Test Method The fused cast corundum refractory materials prepared in the examples and comparative examples were processed into crucible-shaped samples with a central circular hole, the diameter of which was 20 mm and the depth was 25 mm. Then, an equal amount of simulated high-temperature slag was added into the circular hole, and the sample was placed in a high-temperature furnace at 1500℃ for 3 hours to allow the slag to fully contact and react with the sample. After the test, the sample was naturally cooled to room temperature, and then cut along the center of the sample. The maximum erosion depth and erosion area of the slag inside the sample were measured using vernier calipers. The high-temperature erosion resistance of the material was evaluated by the erosion depth. Each group of samples was tested in parallel 3 times, and the average value was taken as the final test result.
[0037] Table 1 Performance test results of the examples and comparative examples
[0038] As shown in Table 1, the refractory materials prepared in the examples and comparative examples exhibit significant differences in thermal shock cycle count, room temperature compressive strength, apparent porosity, and erosion resistance. Among them, Example 2 shows the best performance in all performance indicators, indicating that under median proportions and moderate reaction conditions, a more reasonable synergistic reinforcement system can be formed among the components, which is beneficial for fully utilizing the combined effect of aluminum dihydrogen phosphate-zirconium oxychloride synergistic modification of alumina aggregate and the multiphase reinforcement system.
[0039] Regarding thermal shock stability, Example 2 achieved 33 thermal shock cycles, significantly higher than Examples 1, 3, and the comparative examples. Analysis suggests that the synergistic modification with aluminum dihydrogen phosphate and zirconium oxychloride enhances the interfacial bonding strength between the alumina aggregate and the matrix, reducing the risk of interfacial debonding and microcrack initiation during thermal cycling. Simultaneously, the stabilized zirconium oxide, magnesium oxide, and yttrium oxide create a synergistic toughening effect, effectively mitigating thermal stress concentration and thus significantly improving the material's resistance to alternating thermal shocks.
[0040] Regarding room temperature compressive strength, Example 2 achieved 194 MPa, the highest value among all samples. Examples 3 and 1 achieved 189 MPa and 166 MPa respectively, both higher than the comparative examples. This indicates that the interfacial structure formed by the synergistic modification of aluminum dihydrogen phosphate and zirconium oxychloride can improve melt homogeneity and promote uniform crystal precipitation and stable growth during solidification, thereby increasing the overall density and load-bearing capacity of the material. In contrast, Comparative Examples 1 and 2, due to the use of only a single modification method, had insufficient interfacial strengthening effect, resulting in a significant decrease in compressive strength.
[0041] Regarding apparent porosity, Example 2 showed only 9.3%, significantly lower than Example 1 and all comparative examples. Analysis suggests that calcium phosphate can regulate grain boundary development during melt solidification, promote microstructure homogenization, and reduce solidification defects, resulting in a finer and more uniform microstructure, thus effectively reducing apparent porosity. In Comparative Example 3, after removing calcium phosphate, the apparent porosity increased to 16.3%, indicating that calcium phosphate plays a crucial role in the formation of a fine structure.
[0042] Regarding erosion resistance, the maximum erosion depth of Example 2 was only 3.4 mm, significantly lower than that of Examples 1, 3, and the comparative examples. This is because the synergistic effect of the modified interface structure and the fine microstructure reduced the channels for slag to penetrate along pores and grain boundaries, thus improving the material's barrier ability against high-temperature corrosive media. Simultaneously, the lower apparent porosity and more stable grain boundary structure further enhanced the material's erosion resistance; therefore, Example 2 exhibited the best erosion resistance.
[0043] In summary, this invention, by constructing a synergistic modified alumina aggregate system of aluminum dihydrogen phosphate and zirconium oxychloride, and combining it with calcium phosphate, yttrium oxide, magnesium oxide, and titanium oxide to form a multiphase synergistic reinforcing structure, can significantly improve the thermal shock stability, room temperature compressive strength, and erosion resistance of refractory materials, while effectively reducing apparent porosity. Example 2 achieved the best overall performance, fully demonstrating the significant advantages of this invention's technical solution in constructing a dense structure and improving high-temperature stability.
Claims
1. A dense-structured, highly stable refractory material, characterized in that, The raw materials include the following parts by weight: 80-140 parts of aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina aggregate; 20-80 parts of tabular corundum; 3-20 parts of stabilized zirconia; 1-10 parts of magnesium oxide; 0.5-8 parts of yttrium oxide; 2-15 parts of silica powder; 3-15 parts of calcium phosphate; and 0.5-5 parts of titanium oxide. The aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina aggregate is prepared by synergistic modification of alumina aggregate with aluminum dihydrogen phosphate and zirconium oxychloride.
2. The fine-structured, highly stable refractory material according to claim 1, characterized in that, The aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina aggregate comprises the following raw materials in parts by weight: 80-150 parts alumina aggregate; 3-20 parts aluminum dihydrogen phosphate; 2-15 parts zirconium oxychloride; 30-120 parts ethanol; and 40-150 parts deionized water.
3. A fine-structure, highly stable refractory material according to claim 1 or 2, characterized in that, The preparation method of the aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina aggregate includes the following steps: (1) Add aluminum dihydrogen phosphate to a mixed solvent of ethanol and deionized water and stir to dissolve. Then add zirconium oxychloride and continue stirring to obtain aluminum dihydrogen phosphate-zirconium oxychloride precursor solution. (2) Add aluminum oxide aggregate to the aluminum dihydrogen phosphate-zirconium oxychloride precursor solution for dispersion treatment, so that aluminum dihydrogen phosphate and zirconium oxychloride are uniformly loaded on the surface of aluminum oxide aggregate; (3) The obtained material is aged, filtered, washed and dried to obtain aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina aggregate.
4. The fine-structured, highly stable refractory material according to claim 3, characterized in that, The reaction conditions for step (1) are: stirring at 400-800 rpm for 0.5-3 hours at 50-70°C, followed by adding zirconium oxychloride and continuing the reaction for 1-4 hours.
5. The fine-structured, highly stable refractory material according to claim 3, characterized in that, The reaction conditions for step (2) are to stir and disperse at 500-1000 rpm for 1-5 hours at 60-90℃.
6. The fine-structured, highly stable refractory material according to claim 3, characterized in that, The aging conditions in step (3) are aging at 40-80℃ for 6-24 hours; the drying conditions in step (3) are drying at 100-150℃ for 6-24 hours.
7. The fine-structured, highly stable refractory material according to claim 1, characterized in that, The stabilized zirconium oxide is yttrium stabilized zirconium oxide; the magnesium oxide has a particle size of 1–10 μm; the silicon micropowder has a SiO2 content of 92%–98%; and the titanium oxide has a particle size of 0.1–5 μm.
8. A method for preparing a fine-structured, highly stable refractory material, characterized in that, The preparation method includes the following steps: S1, Weigh and mix aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina aggregate, tabular corundum, stabilized zirconium oxide, magnesium oxide, yttrium oxide, silica powder, calcium phosphate and titanium oxide to obtain basic mixture; S2, the basic mixture is directly added to the electric arc furnace for melting; S3 involves melting the basic mixture in an electric arc furnace for 2 hours and then directly casting it to obtain a fine-structured, highly stable fused cast corundum refractory material.
9. The method for preparing a fine-structured, highly stable refractory material according to claim 8, characterized in that, The reaction conditions for step S1 are to mix and stir at 500-1000 rpm for 1-4 hours at 25-50℃ to obtain a basic mixture.
10. The method for preparing a fine-structured, highly stable refractory material according to claim 8, characterized in that, The reaction conditions for step S2 are as follows: the basic mixture is directly added to the electric arc furnace and melted at 1850-2050℃ for 2 hours; after melting, it is immediately cast into shape.